A Note on the Identification of Common Geographies. (March 2017) - Slez, Adam; O'Connell, Heather A.; Curtis, Katherine J.
Areal data have been used to good effect in a wide range of sociological research. One of the most persistent problems associated with this type of data, however, is the need to combine data sets with incongruous boundaries. To help address this problem, we introduce a new method for identifying common geographies. We show that identifying common geographies is equivalent to identifying components within a k -uniform k -partite hypergraph. This approach can be easily implemented using a geographic information system in conjunction with a simple search algorithm.